2023
DOI: 10.3390/ijms24065747
|View full text |Cite
|
Sign up to set email alerts
|

The Oxidized Lipoproteins In Vivo: Its Diversity and Behavior in the Human Circulation

Abstract: A high concentration of low-density lipoproteins (LDLs) in circulation has been well-known as a major risk factor for cardiovascular diseases. The presence of oxidized LDLs (oxLDLs) in atherosclerotic lesions and circulation was demonstrated using anti-oxLDL monoclonal antibodies. The so-called “oxLDL hypothesis”, as a mechanism for atherosclerosis development, has been attracting attention for decades. However, the oxLDL has been considered a hypothetical particle since the oxLDL present in vivo has not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 105 publications
0
5
0
Order By: Relevance
“…We used CuSO 4 for oxLDL preparation, which is the most widely used method for oxLDL preparation in vitro. However, LDL oxidised with copper may not reproduce the complete features of oxLDL generated in vivo as described previously [ 37 ]. In addition, our findings are limited to a cellular model; further in vivo experiments are required to fully establish the significance of TLR4 signalling in the aetiology of diabetic neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…We used CuSO 4 for oxLDL preparation, which is the most widely used method for oxLDL preparation in vitro. However, LDL oxidised with copper may not reproduce the complete features of oxLDL generated in vivo as described previously [ 37 ]. In addition, our findings are limited to a cellular model; further in vivo experiments are required to fully establish the significance of TLR4 signalling in the aetiology of diabetic neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular uptake of LDL does not result in massive cholesterol accumulation, because intracellular cholesterol downregulates the LDL receptor (LDLr). However, oxidation of LDL in serum or the vascular wall by enzymatic or non-enzymatic mechanisms (lipoxygenases, myeloperoxidases, metal ions) results in the generation of oxidized LDL variants (oxLDL) that do not bind to the LDLr but are internalized by scavenger receptors [81,82]. Scavenger receptors, such as SR-A and CD36, are not downregulated by oxLDL, and mediate massive cholesterol uptake that results in the formation of foam cells [81].…”
Section: Atherosclerosismentioning
confidence: 99%
“…However, oxidation of LDL in serum or the vascular wall by enzymatic or non-enzymatic mechanisms (lipoxygenases, myeloperoxidases, metal ions) results in the generation of oxidized LDL variants (oxLDL) that do not bind to the LDLr but are internalized by scavenger receptors [81,82]. Scavenger receptors, such as SR-A and CD36, are not downregulated by oxLDL, and mediate massive cholesterol uptake that results in the formation of foam cells [81]. Cell-culture studies with human monocytes revealed that oxidized LDL can also induce epigenetic modifications that generate innate memory and result in increased cytokine release after restimulation with toll-like receptor 2 (TLR2) or TLR4 agonists [35].…”
Section: Atherosclerosismentioning
confidence: 99%
“…The most prevalent cardiovascular disease is coronary artery disease (CAD). There is growing evidence that oxidative alteration of lipoproteins is crucial to the development and progression of atherosclerosis (Itabe & Obama 2023). Oxidized low density lipoprotein (oxLDL) has been implicated in CAD progression, promoting inflammation and atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%